Bidirectional associations between mental disorders, antidepressants and cardiovascular disease - Qian Zhao; Fuquan Zhang; Ancha Baranova; Hongbao Cao (BMJ Mental Health, 2024)
Background Mental disorders have a high comorbidity with cardiovascular disease (CVD), but the causality between them has not been fully appreciated.Objective This study aimed to systematically explore the bidirectional causality between the two broad categories of diseases.Methods We conducted Mendelian randomisation (MR) and multivariable MR (MVMR) analyses to evaluate potential causal links between 10 mental disorders, the use of antidepressants and 7 CVDs.Findings We discovered that major depressive disorder (MDD), attention-deficit/hyperactivity disorder (ADHD) and insomnia exhibit connections with elevated risks of two or more CVDs. Moreover, the use of antidepressants is linked to heightened risks of each CVD. Each distinct CVD is correlated with a greater probability of taking antidepressants. Our MVMR analysis demonstrated that the use of antidepressants is correlated with the elevation of respective risks across all cardiovascular conditions. This includes arrhythmias (OR: 1.28), atrial fibrillation (OR: 1.44), coronary artery disease (OR: 1.16), hypertension (OR: 1.16), heart failure (OR: 1.16), stroke (OR: 1.44) and entire CVD group (OR: 1.35). However, MDD itself was not linked to a heightened risk of any CVD.Conclusions The findings of our study indicate that MDD, insomnia and ADHD may increase the risk of CVD. Our findings highlight the utilisation of antidepressants as an independent risk factor for CVD, thus explaining the influence of MDD on CVD through the mediating effects of antidepressants.Clinical implications When treating patients with antidepressants, it is necessary to take into consideration the potential beneficial and detrimental effects of antidepressants.